Analisis Pengaruh Limbah Domestik terhadap Kualitas Air Anak Sungai Asam - G. M Saragih; Hadrah Hadrah; Ekki Prayoga (Universitas Batanghari Jambi, 2022)
The Asam River is one of the tributaries located along the RT 15 area of Paal V Village, the Asam River crossing the residential area of this river has the potential to be polluted by domestic waste. Based on data on the water quality of the Asam River according to the Jambi City Environmental Service in 2020, the water quality of the Asam River has exceeded the surface water quality standard on the parameters of TSS, turbidity, pH, BOD, COD and ammonia. The purpose of the study was to determine the disposal of domestic wastewater and to determine the quality status of the acid river in terms of the pollution index method and to know the plan for controlling the pollution of the acid river with the influence of domestic waste. Based on the calculation of the status of the Asam River water quality, which was determined using the Pollution Index (IP) method, the points AP-1 (Upstream) and AP-2 (Downstream) were in a “Lightly Polluted” condition. This is because the results of the ammonia and turbidity parameter tests at the AP-1 (Upstream) and AP-2 (Downstream) points that exceed the established quality standards. Efforts to control river pollution can be carried out by making riparian buffer strips or planting vegetation on the banks of the Asam River. , the manufacture of communal WWTPs in every existing sub-district along the Asam River and tightening of wastewater quality standards for industrial and domestic activities which must not exceed the water quality standard according to its class.